The Influence of Perception of Fairness, Perception of Organizational Support and Work Environment on Employee Job Satisfaction at Siti Hajar Sidoarjo Islamic Hospital - Akbar, Arshinta Elisya; Abadiyah, Rifdah; Andriani , Dewi (Universitas Pamulang, 2026)
This study aims to analyze the influence of perceived fairness, perceived organizational support, and work environment on employee job satisfaction at Siti Hajar Islamic Hospital, Sidoarjo. The background of the study is based on the importance of job satisfaction as a determinant of performance and quality of health services, amidst the challenges of high workloads and fluctuations in employee discipline. The research method uses a quantitative approach with an explanatory research type, where primary data is obtained through distributing questionnaires to employees, while secondary data comes from company documents. Data analysis was carried out using the Partial Least Square - Structural Equation Modeling (PLS-SEM) technique using SmartPLS 4.0 software. The results of the study are expected to show the extent to which perceived fairness, organizational support, and work environment partially or simultaneously influence employee job satisfaction. These findings are expected to provide theoretical contributions in the development of human resource management science as well as practical benefits for hospital management in designing fairer, more supportive, and conducive policies to improve employee job satisfaction and the quality of health services.